MEDICAL EMERGENCY EXPO: A COMMUNICATION BLUEPRINT FOR PUBLIC PREPAREDNESS IN INDONESIA - Sira, Amaze Grace; Kristiyanto, Haryo Dimasto; Priskila, Loury (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Based on BNPB data in 2024, there were 3,472 disasters in Indonesia, with the highest incidence being hydrometeorological disasters, which was 99.34% and geological disasters, 0.66% of the hydrometeorological disasters that occurred were floods and forest fires, in addition, there were 15 earthquakes and eight volcanic eruptions. In addition to natural disasters, emergencies often happen and claim many lives. According to data from the National Police Traffic Corps, throughout 2023, there were more than 150,000 cases of traffic accidents throughout Indonesia, with the death toll reaching more than 25,000 people. Method: This exhibition was held for 1 day by raising various topics related to disasters and emergencies in Indonesia. This activity not only invited the entire academic community of the Faculty of Medicine, Duta Wacana Christian University, but was also open to the public. Around 300 people attended this event, including UKDW students from medicine, other faculties, and the general public. All participants showed enthusiasm for this expo, from listening to the education provided to watching various theatrical performances and doing (hands-on) the mannequins or tools provided. The part organized by our tutorial group ran smoothly overall. All visitors showed enthusiasm in organizing the activity and participated in the entire series of activities. Keywords: communication strategy, disaster mitigation, emergency, medical, exhibition